Analisis Pengendalian Persediaan Melalui Sistem Pencatatan Penjualan dan Pengelolaan Piutang pada UMKM Toko Sembako Uni Mbobi - Rini Sinamo; Nurwani Nurwani; Yenni Samri Juliati Nasution (Jurnal Riset Akuntansi, 2025)
This study aims to analyze inventory control through sales recording systems and accounts receivable management in MSME grocery stores. The background of this study is based on common problems that occur in grocery stores, namely discrepancies between physical stock and bookkeeping records, manual sales recording, and unorganized and uncontrolled accounts receivable management. These conditions lead to weak inventory control and hamper the smooth running of daily business operations. The research method used is a qualitative approach with a descriptive research type. Data collection techniques were carried out through direct observation, in-depth interviews with business owners, and documentation studies related to business activities. The results of the study indicate that the unstructured sales recording system causes inventory data to be inaccurate, resulting in frequent shortages and excesses of goods. In addition,is not yet optimal  accounts receivable management increases the risk of bad debts, which impacts the turnover of business capital and the procurement process. Therefore, the implementation of an integrated sales recording system and orderly accounts receivable management is necessary for effective inventory control and smooth, efficient, and sustainable business operations.